Industrial applications - Hofrichter, M. (Martin) (The mycota, 2011)
This volume gives a survey of the state of the art in the traditional fields of industrial mycology as well as of selected novel applications of fungi. The first section deals with the use of fungi in the production and processing of bread, cheese, beer and wine, traditional Asian fermentation products and edible mushrooms. The second section is devoted to the production of fungal metabolites and enzymes representing value-added products. In addition to antibiotics, alkaloids organic acids, vitamins and industrial enzymes, which have successfully been in use for decades, it is also dedicated to fungal metabolites, such as insecticidal and nematicidal compounds, immunosurppressants and flavors with promising biotechnological potential. In the next section, the recent developments in fungal biotransformation of small molecules, the bioconversion of lignocelluloses as well as the use of fungi in metal recovery are presented. The final part introduces some innovative new trends in the field of applied mycology: the preparation of fungal bioherbicides, recent genomic approaches for the identification of biopolymer degrading enzymes, current developments in using oxidative enzymes from fungi as well as new attempts to transfer fungal remediation technologies into practice.